(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
The abundance and diversity of insect fauna were studied from two deciduous sal forests of Bhawal and Madhupur located at central part of Bangladesh. A total of 544 individuals of insects of 61 species belonging to 54 genera, 33 families and 11 orders have been identified with Hymenoptera (31%) as the dominant order in species richness followed by Coleoptera (13%), Orthoptera (11%), Diptera (10%), Hemiptera (8%), Lepidoptera (8%), Odonata (8%), Homoptera (3%), Isoptera (3%), Neuroptera (3%) and Dictyoptera (2%). Bhawal scores higher Shannon-Weaver diversity index (Hʹ=3.725) compared to Madhupur (Hʹ=3.340). The Bhawal Sal Forest with the collected 341 (63%) insects and identified 53 (59%) species belonging to 10 orders was found more diverse in species richness than the Madhupur Sal Forest with 37(41%) species belonging to 11 orders identified from the collected 203 (37%) insect samples. Insects of the order Neuroptera were not recorded from Bhawal. Off the 61 species, 29(48%) species were common in both the forests, 24(39%) species were exclusive to Bhawal and eight (13%) species were exclusive to the Madhupur Sal Forest. Apis cerana of Hymenoptera was identified as the dominant species having 9% of the identified samples followed by dipteran species Musca domestica with 6% of the samples. Among the insect species 30 (49%) species were found playing beneficial role as biological control agents, predators, pollinators, honey producers and also organic debris recycler. On the other hand, 31(51%) species were found to be harmful causing damage to forest vegetation as well as human and wildlife at variable degrees. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 11-24